2023
DOI: 10.1021/acs.organomet.3c00366
|View full text |Cite
|
Sign up to set email alerts
|

Living cis-1,4-Selective Polymerization of 1,3-Dienes by Enamino-Oxazolinate Rare-Earth Metal Complexes

Wenyu Shi,
Xuyang Yan,
Xiaoyu Wang
et al.

Abstract: A series of enamino-oxazolinate rare-earth metal complexes were successfully synthesized and structurally characterized. The alkyl elimination of enamino-oxazolinate proligands [R1 = H, R2 = CF3 (L1-H); R1 = Me, R2 = CF3 (L2-H); R1 = i Pr, R2 = CF3 (L3-H); R1 = i Pr, R2 = Ph (L4-H)] with an equimolar amount of Ln­(CH2SiMe3)3(THF)2 (Ln = Y, Lu, Sc) smoothly afforded the desired rare-earth metal complexes [L­(1–4)-Ln­(CH2SiMe3)2]­(THF). Upon activation by a borate, all of these complexes, especially 1-Y, exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…This produced PIP with high molecular weight and narrow molecular weight distribution ( M n = 8.6 × 10 4 g mol –1 , M w / M n = 1.12, entry 1 in Table ). 1 H NMR and 13 C NMR spectra indicated that the generated polymer had highly cis- 1,4 microstructure (96.1%), which was slightly lower than the polymer generated by the corresponding mononuclear yttrium complex (99.6% cis- 1,4) . The reason might be attributed to the steric repulsion of the two enamino-oxazolinate-metal units in 1-Y , as reported in previous literatures .…”
Section: Polymerization Of Isoprenementioning
confidence: 70%
“…This produced PIP with high molecular weight and narrow molecular weight distribution ( M n = 8.6 × 10 4 g mol –1 , M w / M n = 1.12, entry 1 in Table ). 1 H NMR and 13 C NMR spectra indicated that the generated polymer had highly cis- 1,4 microstructure (96.1%), which was slightly lower than the polymer generated by the corresponding mononuclear yttrium complex (99.6% cis- 1,4) . The reason might be attributed to the steric repulsion of the two enamino-oxazolinate-metal units in 1-Y , as reported in previous literatures .…”
Section: Polymerization Of Isoprenementioning
confidence: 70%
“…5 d As its analogous enamino-oxazolinate-based yttrium catalytic system, 1-Y /[Ph 3 C][B(C 6 F 5 ) 4 ]/TIBA also promoted the isoprene polymerization in a living manner. 14 The molecular weight of the obtained PIP increased linearly with both the conversion and monomer feed increasing (Fig. 5 and entries 3, 6–9 in Table 1), and the molecular weight distributions remained narrow ( M w / M n = 1.09–1.10).…”
Section: Resultsmentioning
confidence: 93%
“…Noticeably, the catalytic activity and cis -1,4-selectivity of 1-Y /[Ph 3 C][B(C 6 F 5 ) 4 ]/Al i Bu 3 were comparable to those of its β-diketiminate and enamino-oxazolinate analogues. 5 d ,14 Adding more Al i Bu 3 such as 10 equivalents, the catalytic performance of 1-Y /[Ph 3 C][B(C 6 F 5 ) 4 ]/Al i Bu 3 had no obvious difference to that adding 5 equivalents. Moreover, the 1 H NMR spectrum of mixed 1-Y and 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations